Isolation, purification and identification of 20 – hydroxymaytenin as a bioactive metabolite from Maytenus heterophylla liquid cell culture - Pitakbut, Thanet; Kusari, Souvik; Kayser, Oliver; Spiteller, Michael (Planta medica, 2019)
20 – hydroxymaytenin belongs to the group of quinone - methide petacyclictriterpenes (QMTs), which showed a highly cytotoxicity in wide ranges of cancel cell lines. Therefore, they are pharmaceutical attractive metabolites[1]. However, not all of QMT derivatives are available commercially including 20 – hydroxymaytenin. So, the only way to obtain and used QMTs as a standard reference is to isolate from the plant material. Based on the previous studies, there are two main approaches are available. First method involves in the multiple steps of classical column chromatography[1] and second method is using the preparative HPLC with a suitable column[2]. These methods require either time to process or proper instruments. Here, we propose a short time procedure with regular and basic techniques to isolate and purify 20 – hydroxymaytenin. To modify and establish a fast and simple method to provide accepted in both quality and quantity of 20 – hydroxymaytenin from M. heterophylla cell culture. Overall 35 % yield of high purity (up to 97% by HPLC) of 20 – hydroxymaytenin, confirmed structure by a comparison of a spectroscopic data to the previous report[3], was obtained from this technique after 4 simple steps: extraction with dichloromethane, impurities elimination by solid phase extraction (C-18), isolation by preparative thin layer chromatography and purification by Sephadex LH – 20. Our modified method, which required only a short time of operation and basic equipment, could provide accepted in both quality and quantity of 20 – hydroxymaytenin from M. heterophylla cell cultur